Ketamine infusions for treatment resistant depression: a series of 28 patients treated weekly or twice weekly in an ECT clinic. (June 2014) - Diamond, Peter R; Farmery, Andrew D; Atkinson, Stephanie; Haldar, Jag; Williams, Nicola; Cowen, Phil J; Geddes, John R; McShane, Rupert
Background: Ketamine has a rapid antidepressant effect in treatment-resistant depression (TRD). The effects on cognitive function of multiple ketamine infusions and of concurrent antidepressant medication on response rate and duration are not known. Method: Twenty-eight patients with uni- or bipolar TRD were treated over three weeks with either three or six ketamine infusions (0.5 mg/kg over 40 minutes) in the recovery room of a routine ECT clinic. Post-treatment memory assessments were conducted on day 21 (4–7 days after the final infusion). Patients were followed up for six months where possible, with severity of depression and side effects monitored throughout. Results: Eight (29%) patients responded of whom four remitted. Only three (11%) patients had responded within six hours after a single infusion, but in all responders, the response had developed before the third infusion. The duration of response from the final infusion was variable (median 70, range 25–168 days). Discontinuations included two (7%) because of acute adverse reactions during the infusion and five (18%) because of failure to benefit and increasing anxiety. Ketamine was not associated with memory impairment. The ECT clinic was rated suitable by patients and offered appropriate levels of monitoring. Conclusion: This small, open label naturalistic study shows that up to six low dose ketamine infusions can safely be given within an existing NHS clinical structure to patients who continue their antidepressants. The response rate was comparable to that found in RCTs of single doses of ketamine in antidepressant-free patients but took slightly longer to develop.